Design of a chatbot-based and web schedule management information system to optimize information distribution in the student cadet corps regiment of the Indonesian Defense University - Amelia Kartika; Muhammad Rafi Arnof; Sayyid Hasan Harahap; Rizky Ramadhan Nasution; Henoch Kurniawan; Eryan Ahmad Firdaus (Institute of Computer Science (IOCS), 2026)
The educational environment of the Student Cadet Corps Regiment at the Indonesian Defense University (Unhan RI) requires strict discipline and precise time management; however, the distribution of dynamic schedule information remains inefficient, delayed, and prone to human error due to conventional methods and restricted mobile device usage. This study aims to design and develop an integrated Schedule Management Information System that improves the efficiency, accuracy, and speed of information distribution. The research adopts a system development approach using the Waterfall method, integrating a Web-based Dashboard for schedule management and a Telegram Chatbot for real-time notification, supported by Role-Based Access Control (RBAC) to ensure data integrity and access security. The system was evaluated through Black Box Testing, usability testing using the System Usability Scale (SUS), and performance comparison between conventional and proposed methods involving 25 cadets and 4 staff. The results show that the proposed system significantly reduces schedule distribution time from 30–60 minutes to less than 5 seconds (>95% improvement), increases data accuracy to above 98%, and achieves a SUS score of 82, indicating high usability. These findings imply that the integration of web-based systems and chatbot technology can effectively enhance operational efficiency, support time discipline, and serve as a scalable model for information management in discipline-based institutions with strict operational constraints.